Hominin site distributions and behaviours across the Mid-Pleistocene climate transition in China. (15th November 2020) - Yang, Shi-Xia; Yue, Jian-Ping; Zhou, Xinying; Storozum, Michael; Huan, Fa-Xiang; Deng, Cheng-Long; Petraglia, Michael D.
Abstract: Knowledge about the Early and Middle Pleistocene hominin record of China is steadily increasing owing to the on-going implementation of palaeoanthropological surveys and excavations. Yet, relatively little attention has been paid to the effects of climate variability on hominin populations in China and its influence on archaeological site distributions and hominin behaviours. The Mid-Pleistocene climate transition (MPT), dating to between ∼1.2–0.7 Ma in Eastern Asia, is characterized by significant changes in the length and intensity of glacial-interglacial cycles and in monsoon intensity and terrestrial conditions, which have been implicated in influencing the occupation history of basins within China. Here, the MPT is examined relative to archaeological site distributions across China to determine potential long-term geographic and behavioural effects on hominin populations before, during and after this critical period. Changes in the geographic distribution of hominins are demonstrated across the MPT, with significant shifts in the number of sites in high and low latitudes, likely as a response to changing ecosystems. Technological innovations, including the development of Large Cutting Tools, occur in the MPT and afterwards, possibly a response to the formation of open habitats in South China. Geographic and behavioural shifts in the hominin record challenge traditional views about the long-term, conservative nature of the biological and cultural evolution of hominins in Eastern Asia, and instead demonstrate dynamic responses of populations to ecosystem changes across the Early and Middle Pleistocene. Highlights: An up-to-date review of the Early and Middle Pleistocene hominin record of China. Hominin site distributions changed across the Mid-Pleistocene climate transition (MPT). Technological innovations occurred in the MPT and afterwards. The shifts across the MPT indicate that early hominins were effected by, and responded to ecosystem changes.